Hemodialysis arteriovenous fistula outcomes in elderly patients: a single-centre cohort - Ferreira,Hugo (2018)
The cohort of older age pre-dialysis patients is growing steadily. However, Fistula First may not always be the best strategy due to poorer arteriovenous fistula outcomes in this population. This retrospective cohort study included data from 157 predialysis patients who underwent fistula placement in our centre. Their mean age was 68.1±12.4 years. 64.3% were male and 53.5% were diabetic. The median nephrology follow-up was 3.04 years (IQR: 0.95-5.17). Two groups were created based on patients age at fistula placement: <75 years (n=102) and ≥75 years (n=55). Further analysis is shown, for the younger group vs. the elderly group, respectively. The groups differed only in smoking history (29.4% versus 12.7%, p=0.019) and in hypertensive (3.9% versus 23.6%, p<0.001) and autosomal dominant polycystic kidney disease aetiologies (13.7% versus 0%, p=0.004). Mean estimated glomerular filtration rate at referral for fistula placement was 16.1±4.3 vs. 14.5±4.0ml/min/1.73m2 (p=0.026). Primary fistula failure occurred in 17.6% vs. 32.7%, p=0.032 (RR 1.85 [1.05-3.26]): in 4.9% vs. 5.5% due to thrombosis (p=0.881), in 12.7% vs. 25.5% due to maturation failure (p=0.044; RR 2.0 [1.01-3,94]) and in 2.0% vs. 1.8% due to complications which lead to surgical closure (p=1). During the follow-up period, 52.0% vs. 43.6% patients started hemodialysis (p=0.32). Of these patients, 79.2% vs. 50.0% started hemodialysis with a functioning fistula, p=0.009 (RR 0.63 [0.41-0.96]) while the remaining needed a central venous catheter (RR 2.41 [1.24-4.67]). In multivariate analysis, age ≥75 years and the number of previous fistulawere predictors of failure: OR 3.70 (CI: 1.37-9.98) and 11.65 (CI: 5.04-26.93), respectively. In conclusion, elderly patients had more primary fistula failure. The need of central venous catheter due to non-functioning fistula at time of dialysis initiation was higher in the elderly. Older age (≥ 75 years) and the number of previously placed fistulas seem to predict fistula failure